Historical Change in the Moral Foundations of Political Persuasion. (November 2020) - Buttrick, Nicholas; Moulder, Robert; Oishi, Shigehiro
How have attempts at political persuasion changed over time? Using nine corpora dating back through 1789, containing over 7 million words of speech (1, 666 documents in total), covering three different countries, plus the entire Google nGram corpus, we find that language relating to togetherness permanently crowded out language relating to duties and obligations in the persuasive speeches of politicians during the early 20th century. This shift is temporally predicted by a rise in Western nationalism and the mass movement of people from more rural to more urban areas and is unexplained by changes in language, private political speech, or nonmoral persuasion. We theorize that the emergence of the modern state in the 1920s had psychopolitical consequences for the ways that people understood and communicated their relationships with their government, which was then reflected in the levers of persuasion chosen by political elites.